Fintech Adoption and Financial Agility in Enhancing Distribution Efficiency: A Resource Orchestration Perspective - Iman Supriadi Iman (Universitas Bojonegoro, 2026)
This study examines the influence of financial technology (FinTech) adoption and strategic financial agility on distribution efficiency, with financial flow synchronization as a mediating variable. Grounded in Resource Orchestration Theory (ROT) and Dynamic Capabilities Theory (DCT), the research aims to provide empirical evidence on how digital financial capabilities and agile resource management enhance operational performance in the distribution sector. A quantitative approach was employed, using survey data from 105 logistics and distribution firms in Indonesia. Data were collected via a structured questionnaire with Likert-scale measures and analyzed using Structural Equation Modeling (SEM) in AMOS. Mediation effects were tested via the Sobel test, and construct validity was confirmed through Confirmatory Factor Analysis (CFA). The findings indicate that FinTech adoption and strategic financial agility significantly improve financial flow synchronization, which in turn enhances distribution efficiency. Both direct and indirect effects were significant, with financial flow synchronization acting as a partial mediator. The model demonstrates strong fit indices, supporting the integrated ROT-DCT framework. This study confirms that FinTech and financial agility drive distribution efficiency, but their impact is optimized through synchronized cash flow management. Practical implications include prioritizing FinTech integration and agile financial training for supply chain managers.